Influência de barreiras geográficas na estrutura genética de populações de Aegla uruguayana Schmitt, 1942 (Crustacea, Decapoda, Anomura) - Bitencourt, João Vitor Trindade (2007)
Millions of years ago many species had their populations isolated by geographic barriers, during the formation of the drainage systems of South America Rivers. Modifications in relief lead to the actual formation of the hydrographic basins from Rio Grande do Sul state. Since these basins do not have connection among them, species widely distributed, as Aegla uruguayana Schmitt, 1942, may have their genetic variability being influenced by the watersheds which do not allow gene flow to occur. The aim of this study was to verify the influence of geographic barriers to the genetic structure of different populations of A. uruguayana. The migration patterns of heteroduplex DNA were used to analyze two populations of A. uruguayana from two hydrographic regions of the state (East and West). A significant number of haplotypes was observed in each population, reflecting a high proportion of intrapopulation diversity in AMOVA (49,38%). The geographic barriers seem to be influencing the genetic differentiation of A. uruguayana populations, at least among the populations from Rivers Santa Maria, Ibirapuitã and Camaquã, which had FST values calculated. For the other populations it is necessary to analyze a greater number of individuals, what will make easier the verification of the genetic structure. The utilization of an ultra sensitive molecular marker, such as the microsatellites, will allow a more refined analysis about this question. Thus, microsatellite loci were isolated and characterized. The efficiency of the microsatellite isolation was high and primers were designed for three loci, two of these being polymorphic. Two loci, Au05 and Au13, successfully amplified and were highly polymorphic, with seven and eight alleles, respectively, making them promising for the evaluation of differences among A. uruguayana populations. These loci also successfully cross-amplificated in Aegla longirostri, and have potential for the evaluation of other species from the same gender.